In virtual fashion. - Gray, S. (IEEE spectrum)
Computer graphics and virtual reality are being combined to enable clothes-shoppers to serve as their own clothes models for garments that are digitally fitted and converted into unique 2D patterns. Everything off the rack in effect becomes custom tailoring, choice of fabric and all. The author describes how the virtual reality mannequin is developed from digital images of the body. The virtual design studio is then described. The characteristics of the materials used are incorporated into garment design. The computer modeling of cloth drape is discussed